Efficacy of Regular Maintenance in Mitigating Industrial Equipment Deterioration: Keampuhan Perawatan Rutin dalam Mengurangi Kerusakan Peralatan Industri - Suharto, Muchamad Reysa Pahlewi; Akbar, Ali (Procedia of Engineering and Life Science, 2024)
This study investigates the effectiveness of standardized welding techniques and the impact of regular maintenance on the longevity of factory equipment. Initiated by identifying damage in machinery and equipment, the research involved repairing identified malfunctions as a part of its methodology. Findings indicate that regular inspections and maintenance are crucial in preventing equipment failure. The primary causes of damage were identified as human error, insufficient cleaning practices, and the natural aging of industrial machines. The implications suggest that enhancing maintenance protocols and training for operators could significantly reduce industrial equipment degradation, underscoring the importance of adherence to maintenance schedules in industrial settings. Highlights: Welding techniques compliance with standards is crucial for welders' mastery. Regular inspection and maintenance are essential for damaged factory equipment. Factors causing damage include human error, inadequate cleaning, and machine age. Keywords: Damage, Welding, Maintenance